The use of educational kid web sites as a resource to improve english vocabulary among students of 6th year, at Zoila Alvarado de Jaramillo” school in Loja city, academic period 2014-2015 - Santin Aguirre, Luisa Jhuliana (2016)
This research was carried out with the objective of improving English vocabulary through educational kid websites with the students of the sixth year at "Zoila Alvarado de Jaramillo" School. To perform this research was done using scientific, descriptive, analytic-synthetic and statistical methods. Additionally, tests and questionnaires were used at the beginning and end of the intervention and applied to thirty students as instruments to collect information on the level of students in vocabulary and appreciation on the use of educational websites for children. The main results showed that the application of educational websites as a resource, had a positive effect on improving vocabulary, in the aspects of meaning, form and use since students associated the words with the pictures, they managed to write what they heard and they knew that words or types of words occur in a sentence.